Feasibility of electroacupuncture at Baihui (GV20) and Zusanli (ST36) on survival with a favorable neurological outcome in patients with postcardiac arrest syndrome after in-hospital cardiac arrest: study protocol for a pilot randomized controlled trial - Ruifeng Zeng; Fang Lai; Manhua Huang; Decai Zhu; Baijian Chen; Lanting Tao; Wei Huang; Chengzhi Lai; Banghan Ding (Pilot and Feasibility Studies, 2023)
Abstract Background At present, even the first-line medication epinephrine still shows no evidence of a favourable neurological outcome in patients with sudden cardiac arrest (SCA). The high mortality of patients with postcardiac arrest syndrome (PCAS) can be attributed to brain injury, myocardial dysfunction, systemic ischaemia/reperfusion response, and persistent precipitating pathology. Targeted temperature management, the only clinically proven method in the treatment of PCAS, is still associated with a series of problems that have not been completely resolved. Acupuncture is a crucial therapy in traditional Chinese medicine. On the basis of the results of previous studies, we hypothesize that electroacupuncture (EA) might provide therapeutic benefits in the treatment of PCAS. This study will explore the feasibility of EA on SCA patients. Methods This is a prospective pilot, randomized controlled clinical trial. Eligible patients with PCAS after in-hospital cardiac arrest (IHCA) admitted to our department will be randomly allocated to the control group or the EA group. Both groups will receive standard therapy according to American Heart Association guidelines for cardiopulmonary resuscitation. However, the EA group will also receive acupuncture at the Baihui acupoint (GV20) and Zusanli acupoint (ST36) with EA stimulation for 30 min using a dense-dispersed wave at frequencies of 20 and 100 Hz, a current intensity of less than 10 mA, and a pulse width of 0.5 ms. EA treatment will be administered for up to 14 days (until either discharge or death). The primary endpoint is survival with a favourable neurological outcome. The secondary endpoints are neurological scores, cardiac function parameters, and other clinical parameters, including Sequential Organ Failure Assessment (SOFA) scores and Acute Physiology and Chronic Health Evaluation (APACHE) II scores, on days 0 to 28. Discussion This study will provide crucial clinical evidence on the efficacy of EA in PCAS when used as an adjunctive treatment with AHA standard therapy. Trial registration chictr.org.cn : ChiCTR2000040040. Registered on 19 November 2020. Retrospectively registered. http://www.chictr.org.cn/ .